SCHOOL BASKETBALL: TEACHING GAMES FOR UNDERSTANDING OR TECHNICAL APPROACH ? (Fiep Bulletin - online, 2016)
This paper reports findings of an experimental study about the effects of technical approach and TGfU on game skills, knowledge and game performance in basketball. Two groups of 10- to 11-year-old students participated in the study. A control group was taught by the technical approach and an experimental group by TGfU for 8 weeks. Game skills were measured by Under basket shot test, Dribbling test and Push pass for accuracy test. Procedural and declarative knowledge was assessed by a written test and game performance was assessed by GPAI in 3-3 basketball. Wilcoxon's T-test and Man-Whitney's U-test were used to evaluate the data. As a result both groups improved passing and dribbling skills (p
Keywords: basketball; TGfU; technical approach; physical education